Distribuição espacial de espécies arbóreas na fisiologia de cafeeiros e qualidade de grãos e bebida - Silva Neto, Francisco José da (2019)
Coffee is an important Brazilian commodity. With global climatic changes and consuming market evolution. Shading coffee bushes is gaining notoriety, once shade trees protect coffee bushes from environmental variations and may increase coffee quality. Spatial distribution and shade trees species alter shade and interspecific competition levels, changing coffee bushes responses. This work aims to access shade trees spatial distribution and species effects on physiology and production of ‘IAC Obatã’ coffee, as well as beans and cup quality. The experimental design consisted of randomized blocks with tree repetitions in split-split-plots. Shade trees species formed the plots (Anadenanthera falcata; Cassia grandis; e Peltophorum dubium). Split-plots consisted of five distances from shade trees trunks (coffee bushes on shading trees planting rows, distancing one or five meters from the trunk (D1L and D5L); coffee bushes on shading trees between-rows, parallel to D1L and D5L (D1E and D5E); and PS, coffee bushes distancing 77 meters form shading trees trunks, inflicting on a full sun field).Split-split-plots were due to coffee bushes canopy exposure to the sun (branches facing north or south). Between June/2017 and July/2018 coffee bushes reproductive phenological state was accessed. In April/2018 and September/2018 shading trees overstory density and gases exchanges were estimated with a convex densimeter and an Infrared Gas Analyzer, between 07:00-09:00h and 11:00-13:00h. The equipment registered photosynthetic active radiation (PAR) and gas exchanges. Before harvesting in July/2018, coffee bushes height, canopy diameter, orthotropic brunch diameter, plagiotropic branch length, number and distance between berries rosettes. Yield was expressed in berries (liters) and beans (kilograms). After processing, berries mass, beans mass, sieve retention, beans defects rate and beverage quality were evaluated. Canopy density was not homogenous during the seasons and shifted due to shading trees spatial distribution. PAR was reduced by shade trees to more suitable levels for coffee bushes, specially on shade trees planting rows. The proximity to shade trees trunk decreased analysis chamber temperature. Coffee bushes transpiration as decreases in carbonic assimilation rate during the day was greater in PS. Coffee bushes shaded by P. dubium were taller and wider. Under A. falcata, coffee bushes’ orthotropic brunch diameter decreased due to proximity to the trunk. Berries rosettes distancing was smaller in PS and larger in D1L. Barry production was inferior in D1L and D5L than in PS. Coffee brunches facing north were smaller, bore more floaters and less cherries. P. dubium showed less competition with coffee bushes. The severe water shortage between July and September of 2017 homogenized blossom. In D1L maturation speed differences between branches facing north and south were reduced and favored a better harvesting. Coffee beans shaded by C. grandis were denser. In PS coffee beans were smaller and lighter.